Unconscious, Mysticism and Spirituality - Otón Catalán, Josep (Razón y fe, 2025)
On the occasion of the 25th anniversary of the publication of El inconsciente, ¿morada de Dios? (The Unconscious, dwelling place of God?), the author once again argues the main thesis of the book: the unconscious acts as a mediation in the spiritual experience. Thereby, he distances himself from the positioning of both a mysticism that claims a direct relationship with God and a criticism that reduces spirituality to purely psychic phenomena. This perspective allows for a dialogue with non-confessional forms of spirituality, as well as with the inner life of thinkers and artists. In addition, he also shows how this key idea is strengthened in different official documents of the Church, in the mystical tradition and in biblical testimonies, and he has developed it in his later work.